PENGARUH RASIO TEPUNG MOCAF DAN TEPUNG TEMPE TERHADAP KARAKTERISTIK BROWNIES KUKUS - Herry Dwipayanti; Ni Putu Agustini; Anak Agung Nanak Antarini (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2022)
The mocaf flour substitution research with tempe flour aims to identify organoleptic characteristics, analyze protein and crude fiber levels, and determine the exact ratio of mocaf flour and tempe flour to making steamed brownies. An experimental research design with a randomized block design with 5 levels of treatment and 3 replications. The treatments consisted of P1 (mocaf flour ratio 95%, tempe flour 5%), P2 (mocaf flour ratio 90%, tempe flour 10%), P3 (mocaf flour ratio 85%, tempe flour 15%, P4 (mocaf flour ratio 80 %, tempe flour 20%), P5 (mocaf flour ratio 75%, tempe flour 25%) The results showed that the difference in mocaf flour substitution with tempe flour significantly affected organoleptic quality including color, aroma, texture, taste, overall acceptance , aroma quality, texture quality, crude fiber content and protein content The best treatment of this study was P2 with (90% mocaf flour: 10% tempe flour) with color quality characteristics of 4.13 (likes), aroma 3.92 (likes ), texture 4.12 (like), taste 4.14 (like), with aroma quality 2.80 (not unpleasant), texture quality 2.37 (somewhat soft),overall reception of 4.06 (like) with protein content 9 , 70% bb and 9.22% crude fiber content.Kata Kunci : Tepung Mocaf, Tepung Tempe, Organoleptik, Kandungan Nilai Gizi